2013 IEEE 20th International Conference on Electronics, Circuits, and Systems (ICECS) 2013
DOI: 10.1109/icecs.2013.6815504
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive noise reduction in MIMO-OFDM systems using adaptive receiver structures

Abstract: This paper addresses the performance of MultipleInput-Multiple-Output (MIMO) Orthogonal Frequency Division Multiplexing (OFDM), MIMO-OFDM communication system in environments where the interfering noise exhibits non-Gaussian behavior due to impulsive phenomena. It presents the design and simulation of an adaptive receiver technique that aims to minimize the effect of impulsive noise on the performance of the MIMO-OFDM communication system under Additive White Gaussian Noise (AWGN) channel. The proposed adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Further, for impulsive noise cancellation, copy of impulsive noise was produced and same was subtracted from received signal, is presented in [16] Impulsive Noise suppression in time as well as frequency domain has been proposed for OFDM in [16], where it has been showed that the combined time/frequency domain performs better and significantly reduces the impulsive noise than nonlinear methods under power line communication (PLC) systems. Removal of impulsive noise from multiple-input multiple-output (MIMO) fdm based system using adaptive filters NLMS, RLS and visual sequence Normalized Least Mean Square (VSNLMS) was proposed in [17]. In OFDM based OFDM, the Notch and Least Mean Square methods were proposed for reduction of impulsive noise in [18].…”
Section: Related Workmentioning
confidence: 99%
“…Further, for impulsive noise cancellation, copy of impulsive noise was produced and same was subtracted from received signal, is presented in [16] Impulsive Noise suppression in time as well as frequency domain has been proposed for OFDM in [16], where it has been showed that the combined time/frequency domain performs better and significantly reduces the impulsive noise than nonlinear methods under power line communication (PLC) systems. Removal of impulsive noise from multiple-input multiple-output (MIMO) fdm based system using adaptive filters NLMS, RLS and visual sequence Normalized Least Mean Square (VSNLMS) was proposed in [17]. In OFDM based OFDM, the Notch and Least Mean Square methods were proposed for reduction of impulsive noise in [18].…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [16] presented an adaptive reception technique based on the use of an impulsive noise level detector. On the other hand, the work developed in [17] introduces an alternative solution to the same problem using an adaptive reception technique through adaptive recursive least mean square (RLS), adaptive normalized least mean square (NLMS), and variable stepsize adaptive normalized least mean (VSNLMS) algorithms, which aim to minimize the effect of impulsive noise on the system performance. In [18] the authors used a nonlinear complex Multiple Support Vector Machine Regression (M-SVR) methodology for estimation of fast-fading multipath channel.…”
Section: Introductionmentioning
confidence: 99%